A Comprehensive Model of Knowledge Management Audit in Ministry of Petroleum - Ataollah Jaberansari (Islamic Azad University, Tabriz Branch, 2021)
The present study was conducted by presenting a knowledge management audit model in the Ministry of Oil of Iran. which in terms of practical objectives and in terms of data, exploratory mix (qualitative-quantitative) and in terms of type of study in qualitative dimension, self-emergence data and quantitatively, cross-sectional survey Is. The qualitative population of the study included experts in the field of education, including university professors and senior managers of the Ministry of Petroleum. The sample size consisted of the staff of the staff based on stratified random sampling method and Morgan table of 324 people (163 females and 161 males). In this study, two types of semi-structured interview tools and a researcher-made questionnaire were used to collect the necessary data and information. The face and content validity of the questionnaire was confirmed. Cronbach's alpha coefficient for the questionnaire was 0.90. Qualitative data analysis was performed with the help of open, pivotal and selective coding through interviews, Delphi technique, and brainstorming in 5 dimensions (career goals, coach, environment, student, content, management), 13 components and 80 indicators in the dimension. Qualitative was finalized for the knowledge management audit model and then quantitatively analyzed in two parts: 1- Data description 2- Data analysis. The research findings confirm that the implementation of knowledge management processes in the Ministry of Petroleum, like other organizations without a specific and dynamic knowledge management audit model, will be doomed to failure. The model was calculated and presented by examining the dimensions, components and indicators of knowledge management auditing.